TUGAS DAN FUNGSI JABATAN PENGAJAR JEMAAT DALAM GEREJA MASEHI INJILI DITIMOR (GMIT) - Daud Saleh Luji (Institut Agama Kristen Negeri Kupang, 2022)
The purpose of this article is to find out what the duties and functions of a teaching position are in the Evangelical Christian Church in Timor (GMIT). To get answers from the above objectives, the method used is a qualitative method with a literature study approach. The result is that there are 4 duties and functions of the teaching position as stipulated in the 2010 GMIT Church Administration which are explained in more detail in the Decree of the GMIT Synod No 5/TAP/SIN-GMIT/XXXII/2011 concerning Basic Regulations Concerning the Position and Employees of the Evangelical Christian Church in Timor . Article 36 of the principal regulations above states that there are 4 duties and functions of teaching positions, namely: 1). Carry out teaching activities in the congregation; 2) Organizing the teaching ministry in the congregation; 3). Carry out Christian religious education for sidi members and functional categorical groups; 4). Together with the pastor prepare teaching materials for church members, especially for Children and Youth Ministry (PAR) and catechetical. To clarify these tasks and functions, the authors discuss them with various opinions from a number of literature so as to provide a clearer understanding of the duties and functions of teaching positions in GMIT.